Students’ Speaking Anxiety and Its Effect on Oral Performance in Junior High School - Amanda Ayu Saputri; Rizka Hayati (PROJECT (Professional Journal of English Education), 2026)
Speaking anxiety refers to the fear and nervousness students experience when asked to speak in a foreign language, particularly in front of others. This reaserch aims to analyze how speaking anxiety is reflected in seventh-grade students' speaking performance and to identify the contributing factors. A qualitative case study was conducted involving 15 students from SMP Negeri 7 Pekalongan, selected through purposive sampling. Data were collected using an observation checklist (Horwitz et al., 1986) and an open-ended questionnaire (FLCAS). The findings revealed that all students experienced all three types of speaking anxiety, with test anxiety being the most dominant type, followed by communication apprehension, fear of negative evaluation, and co-dominance of communication apprehension and test anxiety. All students exhibited observable behavioral manifestations such as prolonged silence, stuttering, trembling hands, tense facial expressions, and avoidance of eye contact. The main factors causing anxiety were internal psychological factors, peer pressure, environmental distractions, low self-confidence, and teacher pressure. Speaking anxiety is visibly reflected through students' verbal and non-verbal behaviors. Teachers should recognize these signs and create supportive classroom environments.